Indications for performing nasal allergen challenge - Emeryk, Andrzej; Chełmińska, Marta; Chełmiński, Konrad; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Indications for nasal challenge tests with allergens are divided into diagnostic indications, pathophysiological indications and pharmacological indications. It is important to take the following factors into account to ensure that nasal challenge tests with allergens are carried out properly.